Tinjauan Yuridis Tindak Pidana Pelecehan Seksual Terhadap Perempuan Bersuami: Studi Putusan Nomor 538/Pid.B/2023/PN TJK - Maulana, Irfan; Anggalana, Anggalana (Universitas Islam Negeri Alauddin Makassar, 2024)
Sexual violence is a form of violence caused by sexual problems, and mild sexual violence is a form of verbal sexual harassment. The crime of morality refers to the act of sex. The article that regulates the crime of sexual harassment is contained in the Criminal Code regarding the crime of morality and violation of morality, but the Criminal Code does not recognize it with the term sexual harassment but in the Criminal Code it is referred to as obscene which is regulated by Articles 289 to 296 of the Criminal Code (KUHP). The research methods used in this study are a normative legal approach and an empirical approach. Data processing is carried out through library research such as literature and scientific works related to research problems. The results of this study show that the factors that cause perpetrators to commit sexual harassment crimes against married women are based on Decision Number 538/Pid.B/2023/PN TJK. is a sociative factor that occurs due to the influence of the environment carried out by the perpetrator, the desire that arises by the perpetrator and the opportunity so that it gives rise to the intention and intention to commit the crime. The Judge's consideration in applying criminal sanctions to the perpetrators of the crime of sexual harassment against married women based on Decision Number 538/Pid.B/2023/PN TJK sentenced the Defendant Ardi Santoso Bin Mursalim therefore with a prison sentence of 3 (three) years, the aggravating thing is that the Defendant caused trauma to the victim, the Defendant's actions disturbed the community and the Defendant's actions have not been forgiven by the victim's witnesses. Furthermore, the mitigating factor for the defendant is that the defendant is polite and straightforward in the trial, remorseful and does not repeat his actions, and the defendant has never been punished.